Rice Gall Dwarf Virus Promotes the Propagation and Transmission of Rice Stripe Mosaic Virus by Co-infected Insect Vectors - Jia, Dongsheng; Luo, Guozhong; Shi, Wei; Liu, Ye; Liu, Huan; Zhang, Xiaofeng; Wei, Taiyun (Frontiers in Microbiology, 2022)
Rice stripe mosaic virus (RSMV), a newly discovered plant cytorhabdovirus, and rice gall dwarf virus (RGDV), a plant reovirus, are transmitted by green rice leafhopper Recilia dorsalis in a persistent-propagative manner. In this study, field surveys in Luoding city, Guangdong province of southern China, showed that RSMV and RGDV frequently co-infected rice plants. Furthermore, this co-infection had a synergistic effect on viral replication potential and pathogenicity in rice plants. Meanwhile, RSMV and RGDV also co-infected R. dorsalis vectors, and RGDV significantly promoted the propagation of RSMV in co-infected vectors. Accordingly, co-infection significantly promoted the acquisition and transmission efficiencies of RSMV by R. dorsalis. However, such co-infection did not significantly affect the propagation of RGDV in vectors. More importantly, we also observed that nonviruliferous R. dorsalis preferred to feed on co-infected rice plants, and this process further affected the feeding behavior of R. dorsalis to enhance viral release into rice phloem. These results provided the clues as to why RSMV had been a gradually expanding problem, creating an increasing risk of damage to rice production. Our findings revealed that synergism between RSMV and RGDV in their host and vector enhanced the propagation and transmission of RSMV, which will help guide the formulation of viral control strategies.